Pensamientos irracionales y su influencia en los episodios depresivos de un joven babahoyense - Varandica Briones, Katherine Paola (2020)
Why does that person act that way? This is one of the most common and daily questions that we hear in the course of our lives. Why?. The human being is rewarded for having cognitive processes and one of them is thought, that is to say, the way in which things in our environment are interpreted and seen; it is forged from our childhood according to the environment in which we develop. The thought can be rational or irrational and both have a positive or negative consequence in the life of the subject. The present case study has as its theme irrational thoughts and their influence on depressive episodes in a young Babahoyense and as an objective, to help the patient to counteract irrational thoughts.